Voting for insider trading regulation. An experimental study of informed and uninformed traders’ preferences - Schmidt, Dominik; Stöckl, Thomas; Palan, Stefan (Journal of Banking & Finance, 2024)
Capital markets often regulate insider trading, but whether such regulation aligns with traders’ preferences is an open question. This study examined traders’ regulation preferences conditional on their prospects of becoming informed. Of 64 referenda, traders decided 41 (64%) against regulation. Moreover, traders’ prospects of becoming informed significantly impacted the outcomes of the referenda. In markets in which a group of traders has no chance of receiving inside information, 47% of the referenda are decided against regulation. When all traders could get such information, 81% are. Individual votes reveal that traders who know they will remain uninformed support regulation in 69.27% of the cases, while informed traders do so only 8.33% of the time. Traders who may or may not become informed support regulation 33.33% of the time.